2014
DOI: 10.5294/aqui.2014.14.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention to Reduce the Fear of Falling in Elderly Persons

Abstract: Objetivo: las caídas y el miedo a caerse se relacionan entre sí, siendo cada uno de ellos factor de riesgo del otro. Este trabajo pretende analizar la efectividad de una intervención para reducir el miedo a caer y sus consecuencias dado que la aplicación de este tipo de tratamientos ha mostrado resultados satisfactorios. Método: mediante un diseño cuasi-experimental, con medidas pre-pos, se evaluó a 53 sujetos, con edades comprendidas entre 65 y 89 años y que habían sufrido una caída anterior. La muestra fue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…The pooled data showed a significant difference in the improvement of life satisfaction between the reminiscence therapy and control groups (SMD: 0.40, 95% CI: 0.21, 0.58). For the remaining two studies ( 28 , 36 ) without sufficient data, both reported significant increases in life satisfaction. Therefore, it could be said that reminiscence therapy plays a significant role in the improvement of life satisfaction in older adults ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The pooled data showed a significant difference in the improvement of life satisfaction between the reminiscence therapy and control groups (SMD: 0.40, 95% CI: 0.21, 0.58). For the remaining two studies ( 28 , 36 ) without sufficient data, both reported significant increases in life satisfaction. Therefore, it could be said that reminiscence therapy plays a significant role in the improvement of life satisfaction in older adults ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…The sample size ranged from 24 to 168. Of these studies, six ( 8 , 17 , 26 29 ) were from the United States, three ( 18 , 19 , 30 ) were from Turkey, three ( 9 , 31 , 32 ) were from the Dominican Republic, three ( 33 – 35 ) were from Iran, two ( 36 , 37 ) were from Spain, three were from Malaysia ( 38 ), Australia ( 39 ) and Korea ( 40 ), and seven ( 15 , 16 , 41 – 45 ) were from China. The average age ranged from 65.7 to 84.8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health team uses the results of examinations for the decision of the clinical conduct that best favors the patient's needs. 20 This is probably one of the reasons that make the process of communication between laboratory/unit, clinical analysis, or any mishap, which impede the transfer of results with responsibility, commitment and technical-scientific competence, in order not to compromise the user's care.…”
Section: Discussionmentioning
confidence: 99%
“…Quince estudios fueron realizados con participantes adultos mayores sin problemas serios físicos o mentales (Cantarella et al, 2017;Cuadra-Peralta et al, 2012;Friedman et al, 2017Friedman et al, , 2019Greenawalt et al, 2019;Ishihara et al, 2018;Killen & Macaskill, 2015;Meléndez Moral et al, 2015;Ortega Martínez & Fernández, 2017;Proyer et al, 2014;Ramírez et al, 2013;Salces-Cubero et al, 2019;Sánchez, 2013;Turner et al, 2017;Weiss et al, 2020), cuatro con residentes en casas de retiro (Ho et al, 2014;Jiménez et al, 2016;Meléndez-Moral et al, 2013;Ortega et al, 2015), dos con depresión clínica diagnosticada (Preschl et al, 2012;Taghvaienia & Alamdari, 2019), dos con jubilados o en retiro laboral (Durgante & Dell'Aglio, 2019;Durgante et al, 2020), uno en cuidadores primarios adultos mayores (Bartholomaeus et al, 2019) y uno con participantes con bajo estatus socioeconómico (Weiss et al, 2020). Con respecto a los métodos de reclutamiento, cinco utilizaron publicidad a través de anuncios en periódicos locales, volantes o anuncios en redes sociales y páginas de internet (Cantarella et al, 2017;Friedman et al, 2019;Preschl et al, 2012;Proyer et al, 2014;Turner et al, 2017), 11 acudieron a grupos preformados en casas de retiro o centros comunitarios (Bartholomaeus et al, 2019;Cuadra-Peralta et al, 2012;Ho et al, 2014;Jiménez et al, 2016;…”
Section: Participantesunclassified